1998
DOI: 10.1093/ajcn/68.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acid–supplemented total parenteral nutrition alters intestinal structure, glucose transporter 2 (GLUT2) mRNA and protein, and proglucagon mRNA abundance in normal rats

Abstract: Intestinal adaptation is a complex physiologic process that is not completely understood. Intravenous short-chain fatty acids (SCFAs) enhance intestinal adaptation after 80% enterectomy in rats. The purpose of this study was to examine rapid responses to SCFA-supplemented total parenteral nutrition (TPN) in the normal small intestine. After jugular catheterization, 31 Sprague-Dawley rats (weighing 258 +/- 3 g) were randomly assigned to receive standard TPN or an isoenergetic, isonitrogenous TPN solution supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 36 publications
2
61
1
Order By: Relevance
“…The beneficial effect is the improvement of the leaky gut (reduced permeability), which leads to lower plasma lipopolysaccharide (LPS) and cytokines levels, and consequently a decreased hepatic expression of oxidative stress and inflammatory markers. The knowledge gap here is that while the study of Cani et al is suggestive of a lower level of GLP-2 in ob/ob mice, this is not consistent with the reports that SCFAs are high in the gut of ob/ob mice (21) and SCFAs induce GLP-2 (28,30). Further studies on the interaction between SCFA and GLP-2 and the underlying mechanism may provide an explanation for this inconsistency.…”
Section: Hypothetical Mechanism 1: Elevated Energy Extraction In the contrasting
confidence: 77%
See 1 more Smart Citation
“…The beneficial effect is the improvement of the leaky gut (reduced permeability), which leads to lower plasma lipopolysaccharide (LPS) and cytokines levels, and consequently a decreased hepatic expression of oxidative stress and inflammatory markers. The knowledge gap here is that while the study of Cani et al is suggestive of a lower level of GLP-2 in ob/ob mice, this is not consistent with the reports that SCFAs are high in the gut of ob/ob mice (21) and SCFAs induce GLP-2 (28,30). Further studies on the interaction between SCFA and GLP-2 and the underlying mechanism may provide an explanation for this inconsistency.…”
Section: Hypothetical Mechanism 1: Elevated Energy Extraction In the contrasting
confidence: 77%
“…The underlying mechanisms include the induction of nutrient transporters such as GLUT2 in enterocytes (27,28), the induction of enterocyte proliferation and the inhibition of apoptosis (29). Tappenden et al also noticed that SCFA supplementation induced the expression of ileal proglucagon mRNA and plasma glucagon-like peptide 2 (GLP-2), establishing the current hypothesis that the intestinotrophic effects of SCFAs are mediated by GLP-2 (28,30). Since SCFAs are elevated in the gut of obese patients, they may contribute to the development/ maintenance of obesity through elevated intestinal absorption.…”
Section: Hypothetical Mechanism 1: Elevated Energy Extraction In the mentioning
confidence: 98%
“…The processed form of caspase-3 consists of two active subunits (17 and 12 kDa), which combine to form an active enzyme. Increased cellular abundance of the active subunits of caspase-3 is associated with increased apoptosis (Kothakota et al 1997;Thornberry and Lazebnik 1998). In the current study, active caspase-3 subunit abundance in the distal SI was highest in CV pigs, intermediate in EC pigs (detectable in exp.…”
Section: Proglucagon Expression In Small Intestinementioning
confidence: 99%
“…Tappenden et al [105] showed that SCFA-supplemented TPN rapidly upregulated jejunal GLUT-2 mRNA (glucose transporter 2) and ileal GLUT-2 abundance and ileal proglucagon mRNA. Within the intestinal resection model, SCFAs may exert their trophic effect by extending the duration of increased proglucagon expression.…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%